Prior adaptation improves crude glycerin utilization by cattle - E.H.C.B. Van Cleef; S. Uwituze; C.L. Van Bibber-Krueger; K.A. Miller; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2013)
Crude glycerin has increased in availability as a feedstock for cattle as a result of expansion of the biodiesel industry in the United States. This byproduct, when ingested by cattle, is fermented by ruminal bacteria to yield volatile fatty acids that are used as sources of energy by cattle. The primary component of crude glycerin is glycerol, and the fermentation of glycerol is carried out by specific populations of microorganisms. Anecdotal observations from our previous research with crude glycerin in feedlot cattle have suggested that a period of adaptation may be necessary to achieve optimal utilization of the byproduct. Our objective in this study was to evaluate this adaptive response by measuring in vitro digestion by ruminal microbes that were obtained from cattle fed diets with or without added glycerin.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Cattle; Crude glycerin; Ruminal microbes; In vitro cultures